Primary sensory neuron-specific interference of TRPV1 signaling by adeno-associated virus-encoded TRPV1 peptide aptamer attenuates neuropathic pain. Issue 1 (June 2017) - Xiang, Hongfei; Liu, Zhen; Wang, Fei; Xu, Hao; Roberts, Christopher; Fischer, Gregory; Stucky, Cheryl L; Dean, Caron; Pan, Bin; Hogan, Quinn H; Yu, Hongwei
Background: TRPV1 (transient receptor potential vanilloid subfamily member 1) is a pain signaling channel highly expressed in primary sensory neurons. Attempts for analgesia by systemic TRPV1 blockade produce undesirable side effects, such as hyperthermia and impaired heat pain sensation. One approach for TRPV1 analgesia is to target TRPV1 along the peripheral sensory pathway. Results: For functional blockade of TRPV1 signaling, we constructed an adeno-associated virus (AAV) vector expressing a recombinant TRPV1 interfering peptide aptamer, derived from a 38mer tetrameric assembly domain (TAD), encompassing residues 735 to 772 of rat TRPV1, fused to the C-terminus of enhanced green fluorescent protein (EGFP). AAV-targeted sensory neurons expressing EGFP-TAD after vector injection into the dorsal root ganglia (DRG) revealed decreased inward calcium current and diminished intracellular calcium accumulation in response to capsaicin, compared to neurons of naïve or expressing EGFP alone. To examine the potential for treating neuropathic pain, AAV-EGFP-TAD was injected into fourth and fifth lumbar (L) DRGs of rats subjected to neuropathic pain by tibial nerve injury (TNI). Results showed that AAV-directed selective expression of EGFP-TAD in L4/L5 DRG neuron somata, and their peripheral and central axonal projections can limit TNI-induced neuropathic pain behavior, including hypersensitivity to heat and, to a less extent, mechanical stimulation. Conclusion: Selective inhibition of TRPV1 activity in primary sensory neurons by DRG delivery of AAV-encoded analgesic interfering peptide aptamers is efficacious in attenuation of neuropathic pain. With further improvements of vector constructs and in vivo application, this approach might have the potential to develop as an alternative gene therapy strategy to treat chronic pain, especially heat hypersensitivity, without complications due to systemic TRPV1 blockade.